SELF-ORGANIZATION of MAGNETO-PLASMA STRUCTURES IN UPPER LAYERS OF THE SUN - Chumak, O. V. (Одеські астрономічні публікації, 2017)
The dynamic model of arising and evolution of a solar active region (AR) is proposed. The model realizes diffuse aggregation process of magnetic flux tubes (MFT) in upper levels of the Sun convective zone. Equations of MFT motions subjecting to action of hydrodynamic, magnetic and random forces are discussed. Simulations of MFT diffuse aggregation process based on the equations of MFT motions have been realized. As the result we have received a number of MFT clusters of various sizes and complexity in dependence of initial conditions and values of the model parameters. These results have been compared with observational data. The model has five free parameters: h - typical size of an AR, N - number of MFT, a - typical radius of MFT, d - average magnitude of velocity vector of their random moving, k - ratio of magnitude of vector magnitude of toroidal MFT field to poloidal one. Values of poloidal field of all MFT were let to be equal and constant. Variation of these parameters results in arising of MFT clusters of various types, and, accordingly, to various values of fractal, informational and correlation dimensions of the resulting magnetic field. Parameters of the model have been selected in such a way that all three of the dimensions correspond to observed ones in real ARs. As an example, for AO 10488, which arisen and developed into complete con- figuration near central meridian, there was shown that good numerical correspondence among the mentioned scaling properties is observed under the next value of the free parameters of model: h ≈ 150Mm, N from 50 to 300, for various time of evolution, a ≈ 300km; d ≈ 20km/c, k ≈ 0.01. Variations of the free model parameters in physical reasonable limits allow getting all magnetic and morphological types of ARs. It is shown, that the simulation results correspond to observational data, confirm and define more exactly the base points of Parker’s ’spaghetti’ model.